Applying the double observer methodology for assessing blue sheep population size in Nar Phu valley, Annapurna Conservation Area, Nepal. Issue 4 (15th October 2021) - Thapa, Kamal; Jackson, Rodney; Gurung, Lalu; Acharya, Hari Bhadra; Gurung, Raj Kumar
Abstract : This study was undertaken in spring, 2019 to assess the applicability of the double‐observer survey method for estimating blue sheep Pseudois nayaur abundance in Nar‐Phu valley of Manang District located in Annapurna Conservation Area of northern Nepal. Since counting large mammals in rugged mountain habitat poses a special challenge, we tested the efficacy of the double observer method for generating robust population estimates for this important protected area. The overall detection probability for observers (O1 and O2) was 0.94 and 0.91 for a total of 106 groups comprised of 2059 individual blue sheep. We estimated the area's blue sheep population at 2070 (SE ± 168.77; 95% CI 2059–2405) for the 246.2 km 2 of sampled habitat. We determined blue sheep to be widely distributed within the study area with a mean density of 8.4 individuals per km 2 based on a total study area of 246.2 km 2 . We discuss demographic population structure and identify limitations when applying the double observer approach, along with recommending viewshed mapping for ensuring more robust density estimates of mountain‐dwelling ungulates like blue sheep or ibex that inhabit extremely heterogeneous terrain which strongly influences sighting distances and overall animal detection rates.